Taxonomy and phylogenetic position of Phragmidium altaicum, a newly described rust fungus on Rosa, based on molecular and morphological data - Liu, Yun; Ono, Yoshitaka; Kakishima, Makoto; Gafforov, Yusufjon; Liang, Ying-Mei (Phytotaxa, 2019)
Phragmidium altaicum, a new causal fungus of a rose rust disease, is described and illustrated. The species, collected in Xinjiang Province, northwestern China, is well distinguished by its morphology and rDNA LSU and ITS sequences from the other Phragmidium species on Rosa. The new rust species is characterized primarily by 4–7-celled teliospores, bearing robust verrucae on the surface, aeciospore-surface structure of ‘Echinulate type 4,’ and urediniospore surface completely covered with echinulae with inapparent mushroom-shaped base. The sequence analysis showed that this species is closely allied to P. tuberculatum, but they differ in their morphological characteristics.